METHODOLOGICAL APPROACHES TO ASSESSING THE ASSOCIATION BETWEEN DENTAL HEALTH AND QUALITY OF LIFE IN WOMEN EMPLOYED IN THE CHEMICAL INDUSTRY - Ibragimova Feruza Ikromovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. Today, the study of people's quality of life is one of the important parts of medical research. It is known that society is constantly changing, and at the same time, people's attitudes towards health and health care are also changing. At the heart of this is the understanding of the social consequences of the disease on the one hand, and on the other hand the realization that medical treatments are aimed at prolonging human life and improving the quality of life. Therefore, the quality and efficiency of health care work is evaluated according to its impact on the quality of life of patients.